Early Mobilization Post Acute Stroke Thrombolysis and/or Thrombectomy Survey. (April 2023) - Silver, Brian; Demers-Peel, Meaghan; Alexandrov, Anne W.; Selim, Magdy H.; Bernhardt, Julie
Background: We sought to determine mobilization practices following emergency stroke therapy in centers across the United States. Methods: We surveyed hospitals in the NIH StrokeNet regarding mobilization practices following acute stroke thrombolysis and/or thrombectomy. An anonymous survey was sent out to all StrokeNet sites Survey questions included stroke center designation, location of admission, whether a formal bed rest protocol was in place, minimum bed rest period required, which person first mobilized the patient. Results: 48 centers responded to the survey including 45 Comprehensive Stroke Centers and 3 Primary Stroke Centers. Most patients were admitted to a neuro-intensive care unit (54%), others to a general medical/surgical ICU, stroke ward, or combination. 60% of respondents indicated that a formal bed rest policy was in place. Minimum bed rest requirements after thrombolysis alone ranged from 0 to 24 hours (35% with a 24-hour bed rest protocol, 19% with no minimum, 13% with a 12-hour minimum, 4% with an 8-hour minimum, 4% with a 6-hour minimum, and 6% with a variable rest period). Similar variations were reported in patients undergoing thrombectomy with ranges from 0 to 24 hours bed rest. First mobilization was by a nurse 52% of the time and by a physical therapist 48% of the time. Conclusions: Mobilization practices following emergency ischemic stroke reperfusion treatments vary significantly across stroke centers. Mobilization of patients is performed primarily by nurses and therapists. Further study regarding an optimal approach for mobilization following acute ischemic stroke thrombolysis and/or thrombectomy is warranted.